Local Probiotic Therapy with Lactobacillus plantarum Mitigates Scar Formation in Rabbits after Burn Injury and Infection - Satish, Latha (Surg Infect (Larchmt), 2017)
Background: Infection is the most common complication in burn-injured patients and is believed to contribute to the hypertrophic scarring frequently observed in such injury. Pseudomonas aeruginosa is a common pathogen in burn wound infection. We examined the effect of local probiotic therapy with Lactobacillus plantarum on the severity of the scarring following burn wounding and infection with P. aeruginosa in a rabbit model. Methods: Full-thickness burn wounds were inoculated with control vehicle or L. plantarum; wounds were then challenged with bioluminescent P. aeruginosa. The time course of the ensuing infection was monitored by quantification of the emitted light. After allowing wounds to contract to near completion, they were harvested and analyzed for markers of scar formation. Results: Application of L. plantarum curtailed both the severity and the length of the pseudomonal infection. Probiotic therapy significantly reduced both Type I collagen mRNA concentrations and total collagen protein accumulation in infected wounds, consistent with reduced scarring. Surprisingly, the probiotic showed a nearly equivalent effect in uninfected wounds. Masson's trichrome staining confirmed these findings histologically. Conclusions: Lactobacillus plantarum shows exciting potential as a therapeutic agent to both counteract burn wound infection and to alleviate scarring even in the absence of infection.